Indirect to Direct Charge Transfer Transition in Plasmon‐Enabled CO2 Photoreduction. Issue 2 (12th November 2021) - Zhang, Yimin; Yan, Lei; Guan, Mengxue; Chen, Daqiang; Xu, Zhe; Guo, Haizhong; Hu, Shiqi; Zhang, Shengjie; Liu, Xinbao; Guo, Zhengxiao; Li, Shunfang; Meng, Sheng
Abstract: Understanding hot carrier dynamics between plasmonic nanomaterials and its adsorbate is of great importance for plasmon‐enhanced photoelectronic processes such as photocatalysis, optical sensing and spectroscopic analysis. However, it is often challenging to identify specific dominant mechanisms for a given process because of the complex pathways and ultrafast interactive dynamics of the photoelectrons. Here, using CO2 reduction as an example, the underlying mechanisms of plasmon‐driven catalysis at the single‐molecule level using time‐dependent density functional theory calculations is clearly probed. The CO2 molecule adsorbed on two typical nanoclusters, Ag20 and Ag147, is photoreduced by optically excited plasmon, accompanied by the excitation of asymmetric stretching and bending modes of CO2 . A nonlinear relationship has been identified between laser intensity and reaction rate, demonstrating a synergic interplay and transition from indirect hot‐electron transfer to direct charge transfer, enacted by strong localized surface plasmons. These findings offer new insights for CO2 photoreduction and for the design of effective pathways toward highly efficient plasmon‐mediated photocatalysis. Abstract : Upon illumination, hot electrons generated by the plasmon decay around the silver clusters transfer into the molecular orbitals of CO2, resulting in activation of the asymmetrical stretching and bending mode of CO2 and leading to its final splitting. Cooperative interaction and transition from indirect hot‐electron transfer to direct charge transfer cause the nonlinear relationship between laser intensity and reaction rate.